Agent-based computational modelling: Facing complexity - Coelho, Helder (2018)
The analysis of social and dynamical systems faces a paradigm shift, from mathematical methods to agent-based simulation. It is a new line of thinking, multidisciplinary, where technological and conceptual innovations grow, and where artificial societies of individual and intelligent agents are generated to replicate simple and plausible human beings. This paper deals with agent models and the ways how simple rules of social interaction grow explanations of complex behaviors. Through two examples (technological innovation in a science park and design of tax compliance policies) we show how Swarm and NetLogo tools were explored to model real worlds.